The i-CanManage program to improve exercise and symptom management for Vietnamese women after cancer: A pilot randomized controlled trial protocol - Huyen Thi Hoa Nguyen; Linh Khanh Bui; Tran Ngoc Tran; Ngan Thi Thuy Nguyen; Anh Hoang Phuong; Hieu Huy Pham; Andrew W Taylor-Robinson; Tran Quang Duc; Huong Thi Thanh Nguyen (Digital Health)
Background Women dealing with cancer often face a myriad of physical and psychological challenges. Regular physical activity and mobile applications offering healthcare consultation, information, and health tracking have shown promise in aiding this demographic. Therefore, this study aims to examine the effectiveness of the i-CanManage program in improving physical activity, self-efficacy in symptom management, and the quality of life (QoL) among Vietnamese women after completion of cancer treatment. Methods A two-arm pilot randomized controlled trial will be conducted. Eligible participants will be randomly allocated to intervention and control groups. Members of both groups will be provided with a Cancer Management Handbook containing information on Life After Cancer and Symptom Management. Intervention group participants will be offered a 12-week personalized exercise program called i-CanManage via a Cancer Wellness Program smart application—an artificial intelligence-based mobile app developed for monitoring patients’ symptoms with a Fitbit Charge 5 wearable device. Data will then be collected at weeks 0, 6, and 12 concerning physical activity, symptom severity, self-efficacy, self-care, and QoL. App usability and user experience will also be explored using both quantitative and qualitative methods. Discussion This pilot study will assess the effectiveness of the internet-based cancer management program on physical activity, self-efficacy in symptom management, and QoL of women following cancer treatment in Vietnam, as well as evaluate users’ experience with the smart app. The findings will contribute to the growing evidence on the role of mhealth in oncology care, providing insights into how technology-driven interventions can empower patients in their cancer recovery journey. Datasets collected from this study will be openly available to the research community to foster new advances in the field.